Dinamika Urban Heat Island di Kawasan Perkotaan Yogyakarta - Fathurrohmah, Septiana; Candra Kurniati, Ayu (ReTII, 2022)
Yogyakarta City intensively has experienced a spatial pressure which triggered urban agglomerations known as the Yogyakarta Urbanized Area. Built up area domination as the main feature of urban area continuously expanded to the districts which directly adjacent to the City of Yogyakarta. The increasing of built up area followed by environmental imbalances can trigger various social dan urban environmental problems. One of these problems is about thermal amenities which can be associated with the Urban Heat Island phenomenon. This study aims to obtain an overview of the dynamics of Urban Heat Island phenomenon in Yogyakarta Urbanized Area through GIS analysis of Landsat-8 satellite imagery data in 2015 and 2020. the results of analysis indicate that the Urban Heat Island phenomenon has occurred in Yogyakarta Urbanized Area. In the period of observation, Urban Heat Island has increased both in value and extent. Spatially, the relatively higher value of Urban Heat Island is located in the center of urban (Yogyakarta City area) and extends towards the northeastern side of the city. These areas can be used as reference for management priorities to realize the thermal amenities of urban environment.